A 4-month-old boy with gastrointestinal stromal tumor of mesocolon. Issue 1 (2nd January 2019) - Jing, Xuquan; Meng, Xue; Gao, Yongsheng; Yu, Jinming; Liu, Bo
ABSTRACT: Gastrointestinal stromal tumors (GISTs) are very uncommon in pediatric patients, and they are distinct clinical-pathological and molecular deviations from their adult counterparts. Most pediatric GISTs lack the c-kit or platelet-derived growth factor receptor alpha (PDGFRA) genes mutations. To date, there is no published standard guidelines available for the best treatment of pediatric GISTs, especially for infant GIST. Therefore, we report a case of 4-month-old infant with GIST of mesocolon without KIT/PDGFRA mutation. We also review the clinical, biological, and genetic features of pediatric GISTs and re-think several questions that could affect clinical practice.